Relationship between the serum levels of Vitamin D and inflammatory markers in ESRD patients - Etminan, Abbas; Seyed Askari, Seyed Mostafa; Naghibzade Tahami, Ahmad; Adel Mahdi, Seyed; Behzadi, Mina; Shabani, Mohammad (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: In patients with End-stage renal disease (ESRD), 25-(OH)-Vitamin D3 deficiency is a common problem and also the inflammatory responses increase in these patients. The present study aims to evaluate the relation of 25-(OH)-Vitamin D3 with the indirect inflammatory markers in patients on hemodialysis (HD) and peritoneal dialysis (PD). Methods: This study was done by cross-sectional method on 85 ESRD patients receiving renal replacement therapy (RRT), from one geographical area. 64 patients on HD and 21 patients on PD who were matched for age and sex were studied. Serum level of 25-(OH) Vitamin D3 was measured in each patient. ESR, CRP and the other routine blood tests were measured as well. Results: The level of 25-OH Vitamin D3 was significantly lower in PD group in comparison to HD group (P: 0/0012, 2/70±0/10 vs 2/05±0/14). Platelet (195/40 ± 7/6 vs 265/52 ± 15/6, P: 0/001) and ESR (46/80 ± 6/89 vs 23/53 ± 1/96, P: 0/003) were significantly higher in PD group. Considering total population of the study (PD and HD), there was a significant association between ESR and serum level of 25-(OH)-Vitamin D3 (r: 0.26, P: 0.036) but no correlation was seen between 25-(OH)-Vitamin D3 and hemoglobin (Hb) or duration of dialysis. On the other hand, in patients on HD, multiple regression analysis revealed a significant relationship between duration of dialysis (P: 0.02), Hb (P: 0.01) and ESR (P: 0.001) with 25-(OH)-Vitamin D3 level. Moreover, there was a relationship between vitamin D3 levels and inflammatory markers as well. Conclusions: The deficiency of 25-(OH)-Vitamin D3 was followed with increase of ESR as an inflammatory marker in patients on HD. Key words: Inflammation; 25-hydroxy vitamin D; Renal replacement; Dialysis